Primary Endometriosis of Umbilical Scar: Case Report and Review of Literature. Issue 1 (January 2014) - Vignali, Michele; Ciocca, Erika; Alabiso, Giulia; Di Prun, Allegra Barbasetti; Scagnelli, Giuseppe; Natale, Andrea; Solima, Eugenio; Busacca, Mauro
We report a case of umbilical endometriosis and review the literature about the finding. The patient was a 39-year-old woman who presented with 6 months of umbilical bleeding and pain during the first day of her period. A soft tissue ultrasound scan showed 2 superficial solid masses within the periumbilical subcutaneous adipose tissue, suggestive for ectopic endometriosis localization. We decided to remove the umbilical nodules, excising 1 cm of the surrounding tissue. Reports in the literature indicate cases of umbilical endometriosis in about 0.5%-1% of women with endometriosis.